2012
DOI: 10.3389/fnhum.2012.00214
|View full text |Cite
|
Sign up to set email alerts
|

Facial mimicry and the mirror neuron system: simultaneous acquisition of facial electromyography and functional magnetic resonance imaging

Abstract: Numerous studies have shown that humans automatically react with congruent facial reactions, i.e., facial mimicry, when seeing a vis-á-vis' facial expressions. The current experiment is the first investigating the neuronal structures responsible for differences in the occurrence of such facial mimicry reactions by simultaneously measuring BOLD and facial EMG in an MRI scanner. Therefore, 20 female students viewed emotional facial expressions (happy, sad, and angry) of male and female avatar characters. During … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
125
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(138 citation statements)
references
References 54 publications
12
125
0
1
Order By: Relevance
“…It is still an open question whether the lack of EMG activity reflects an inability in this group to both mimic and to react emotionally to facial stimuli. Some explanation comes from a recent study in which BOLD and facial EMG were simultaneously measured in an MRI scanner (Likowski et al, 2012). It was shown that congruent facial reactions recorded from CS and ZM during passive perception of static happy, sad, and angry facial expressions corresponded to activity in prominent parts of the MNS (i.e., the inferior frontal gyrus), as well as areas responsible for emotional processing (i.e., the insula).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is still an open question whether the lack of EMG activity reflects an inability in this group to both mimic and to react emotionally to facial stimuli. Some explanation comes from a recent study in which BOLD and facial EMG were simultaneously measured in an MRI scanner (Likowski et al, 2012). It was shown that congruent facial reactions recorded from CS and ZM during passive perception of static happy, sad, and angry facial expressions corresponded to activity in prominent parts of the MNS (i.e., the inferior frontal gyrus), as well as areas responsible for emotional processing (i.e., the insula).…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, neuroimaging data (Trautmann et al, 2009; Arsalidou et al, 2011; Kessler et al, 2011) has revealed that the perception of dynamic compared to static stimuli engaged not only motor- (e.g., inferior frontal gyrus) (Carr et al, 2003), but also brain regions associated with emotion (e.g., amygdala, insula). These regions are also considered to be part of the extended mirror neuron system (MNS) (van der Gaag et al, 2007; Likowski et al, 2012), a neuronal network linked to empathy (Jabbi and Keysers, 2008; Decety, 2010a; Decety et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Thus, corrugator EMG recordings constitute an adequate valence-sensitive measure for emotion researchers who seek to unobtrusively validate that affective changes are successfully induced in emotion-elicitation paradigms conducted in the laboratory. Despite its utility, only recently has this measure been successfully incorporated during functional neuroimaging recordings in emotion processing (Heller et al, 2011) and facial mimicry paradigms (Likowski et al, 2012). By taking advantage of a bunched slice acquisition sequence developed in our laboratory, we were able to examine how moment-to-moment increases and decreases in negative affect (as manifested by modulation of the corrugator supercilii muscle) were associated with corresponding changes in neural activity.…”
Section: Discussionmentioning
confidence: 99%
“…Schilbach, Eickhoff, Mojzisch, and Vogeley (2008) reported increased brain activity, likely accompanying facial mimicry, in the face area of the left primary motor cortex (M1) and in the bilateral posterior cingulate gyrus. Likowski et al (2012) reported significant correlations between the amplitude of facial mimicry and brain activity in various areas that belong, or are functionally connected, to the MNS, including the IFG, the SMA, the insula, the medial temporal gyrus (MTG) and the superior temporal sulcus (STS). Also of interest, the disruption of medial premotor cortices with event-related rTMS interferes with the recognition of facial expressions (Balconi & Bortolotti, 2013a, 2013bRochas et al, 2013), while activation of a more fronto-polar area (BA9) increases facial mimicry (Balconi & Canavesio, 2013).…”
Section: Introductionmentioning
confidence: 99%